Mobile commerce and its apps - opportunities and threats in Malaysia - Yousef A. Baker, El-Ebiary; Julaily Aida, Jusoh; Mohd Hafiz, Yusoff@Che Abdullah (2021)
The purpose of this study is to discuss on opportunities and threats of Foodpanda as an online Ecommerce platform including their strength and weaknesses. Electronic Commerce commonly known as E - Commerce means buying and selling of goods and services through internet. Ecommerce is a way of conducting business online. Though e- commerce is facing challenges in the market but it has scope to outsource the traditional markets. Nowadays, E- commerce is a very big and potential platform in business organization. There are so many platform of E- commerce and one of them is Foodpanda. Foodpanda is one of the leading online food delivery marketplaces and is spread out globally. Its main job is to enable users to place orders at nearby restaurants with the assistance of its website or via its mobile app. A study on Foodpanda will show on opportunities and threads of Foodpanda as one of the biggest online E- Commerce platform.